MODELLING AND OPTIMIZATION DESIGN FRAMEWORK AND LAYOUT MICROSATELLITE EARTH OBSERVING - M. A. Starasotnikau; R. V. Feodortsau (Приборы и методы измерений)
Proposed structure and layout of the target and on-board equipment microsatellite for remote sensing of the Earth, taking into account its impact on the main disturbing factors occurring in the derivation and operation of spacecraft in orbit. Recommendations on the choice of optimal design of micro power skeleton, based on modeling the impact on his body external loads.